DISCOURSE OF VIOLENCE AGAINST WOMEN IN THAI MASS MEDIA: A TRANSMISSION OF PATRIARCHY THROUGH THE LANGUAGE - Neunghathai Khopolklang; Weerapong Polnigongit; Nisachol Chamnongsri (The Indonesian Journal of Communication Studies, 2015)
Since its beginnings, feminism has studied the relationship between men and women which is based on sexual inequality.  It indicated that the needs of men to dominate women has lead to sexual violence at present.  This concept, sometimes called ‘Patriarchy’, was implemented almost at the same time as the beginning of urbanization.  Patriarchism is the concept that men have the power to oppress women.  It is the power in society, ideology, family, and the political system which men use to oppress directly or through worship, law, language, custom,  idioms, education as well as the division of labour in which women are always less powerful.  Patriarchism is the system by which men use the law, culture and religion to give them the confidence that they have more power than women.  Therefore, they use violence because women are lower in status and they need women to be lower in status.  This also affects men’s need to overcome their sense of alienation caused by women’s fertility whereby women give birth and raise children.  This article focuses on the discourse about violence against women through the language of various Thai media, which reflects the transformation of the patriarchy mechanism to the social truth establishment by the media.